A SOCIAL ACTION ANALYSIS OF NEWS ON 2011 WAR IN LIBYA: REPRESENTATION OF THE US ALLIANCES ON ONLINE USA TODAY AND THE TRIPOLI POST - Rusyda, Arini (2014)
This paper reveals the representation of social actions of news discourse regarding 2011 War in Libya on online USA Today and The Tripoli Post. Social actions refer to a set of actions and reactions of nine main social actors involved in the war news reports, especially the US Alliances (President Obama, NATO, US Administration (White House), US Military (Department of Defense)). The research employs van Leeuwen's (2008) framework on Representing Social Actions to analyse those social actions through two stages, by classifying the categories and discovering the distribution of the transformations. The results indicate that USA Today presents 288 actions, 39 reactions and 187 transformations, while, Tripoli Post attributes 262 actions, 18 reactions and 112 transformations. US Alliances, on both media, are assumed to build legalization on war issue by being represented in positive quality transformation through objectivated and deagentialized social actions, which allow their social actions to be subtilized. In addition, quotations and renditions belong to them are dominantly mentioned, suggesting their power of dominance within the texts. This dominance is supported by their representation as the one that coping with the war in cognitive and perceptive reactions, illustrating them as rational, thinkers in contrast to civilians and rebels who are represented in more emotive reactions (affective). It indicates that both media tend to be biased in representing social actors involved by means of their attributed social actions. Keywords: CDA, Representation, 2011 War in Libya, US Alliances Makalah ini membahas tentang representasi aksi sosial dalam wacana berita mengenai 2011 Perang di Libya pada portal berita online USA Today dan The Tripoli Post. Aksi sosial tersebut mengacu pada serangkaian aksi dan reaksi dari sembilan aktor sosial utama yang terlibar dalam wacana berita terpilih, terutama Aliansi AS (Presiden Obama, NATO, Pemerintahan AS (Gedung Putih), Militer AS (Departemen Pertahanan)). Penelitian ini menggunakan kerangka pemikiran van Leeuwen (2008) tentang Representing Social Actions untuk menganalisis aksi-aksi sosial melalui dua tahapan, dengan mengelompokkan kategori aksi dan menganalisa distribusi transformasi aksi-aksi tersebut. Hasil penelitian menunjukkan bahwa USA Today menyajikan 288 aksi, 39 reaksi dan 187 transformasi, sementara, Tripoli Post mengatribusikan 262 aksi, 18 reaksi dan 112 transformasi. Aliansi AS, pada kedua media, diasumsikan tengah membangun legalisasi isu perang dengan adanya transformasi positif pada aksi sosial melalu objektivasi dan deagentialisasi, yang kemudian memungkinkan aksi sosial mereka diperhalus secara literal. Selain itu, kutipan yang diutarakan AS dominan disebutkan, menunjukkan penguatan posisi mereka dalam teks. Dominasi ini didukung dengan adanya representasi mereka sebagai salah satu pihak yang menghadapi perang dalam reaksi kognitif dan perseptif, menggambarkan Aliansi tersebut sebagai pihak yang rasional, pemikir, berbeda dengan warga sipil dan pemberontak yang direpresentasikan dengan reaksi yang lebih emotif (afektif). Hal ini menunjukkan bahwa kedua media cenderung bias dalam merepresentasikan aktor sosial yang terlibat melalui aksi sosial mereka. Kata kunci: CDA, Representasi Perang Libya 2011, Aliansi AS